2012
DOI: 10.1111/j.1463-1326.2011.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

The increased dipeptidyl peptidase‐4 activity is not counteracted by optimized glucose control in type 2 diabetes, but is lower in metformin‐treated patients

Abstract: DPP-4 activity is increased in T2D, but is not lowered by glucose control, suggesting that hyperglycaemia is not a direct determinant of DPP-4 activity. However, metformin may indirectly reduce DPP-4 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 21 publications
6
43
2
1
Order By: Relevance
“…In PACs isolated from T2D patients compared to healthy control PACs, we found significantly altered expression of BCL2, CDKN1A, VCAM1, ICAM1, ITGB2 and DPP4 (Figure  3A). Importantly, as previously noted [21], DPP4 expression was markedly increased in diabetic PACs, providing a rationale for pharmacologic DPP-4 inhibition. Expression of the selected genes in the entire PACs culture was unaffected by treatment with Saxagliptin and/or SDF-1α (not shown).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In PACs isolated from T2D patients compared to healthy control PACs, we found significantly altered expression of BCL2, CDKN1A, VCAM1, ICAM1, ITGB2 and DPP4 (Figure  3A). Importantly, as previously noted [21], DPP4 expression was markedly increased in diabetic PACs, providing a rationale for pharmacologic DPP-4 inhibition. Expression of the selected genes in the entire PACs culture was unaffected by treatment with Saxagliptin and/or SDF-1α (not shown).…”
Section: Resultssupporting
confidence: 71%
“…This can be attributed to the marked upregulation of DPP-4 gene expression in diabetic PACs. We have previously shown that DPP-4 activity is increased in serum/plasma of T2D compared to non-diabetic patients and is not directly related to glucose control [21]. DPP-4 exists as either a soluble or membrane bound (cellular, CD26) isoform and the relative contribution of the 2 to the total DPP-4 activity and its biological effects were previously unknown.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-4 activity, however, is more closely associated with factors related to obesity and insulin resistance than to glucose level in type 2 diabetic patients [24,25,27]. Moreover, elimination of hyperglycemia did not change the plasma DPP-4 activity in patients with type 2 diabetes [28]. These data implied that hyperglycemia per se might not be a major regulator of DPP-4 activity in the circulation.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, it has been reported that the degree of plasma DPP4 activity was significantly higher in obese subjects than in lean subjects [14,15]; however, the DPP4 hyperactivity in obese individuals did not seem to be affected by their degree of overweightedness [14]. Moreover, it has been reported that the degree of plasma DPP4 activity was affected by widely used anti-diabetic agents, such as metformin [16], and ageing [12]. Taking these findings together, it might be difficult to define the relationship between DPP4 activity and the levels of blood glucose and BMI (body mass index) because of the diverse clinical backgrounds of subjects; therefore, data from healthy young subjects would help us to identify whether DPP4 activity is physiologically involved in diabetes and/or obesity.…”
Section: Resultsmentioning
confidence: 99%